New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae) - Kvifte, Gunnar Mikalsen; Ivković, Marija (Zootaxa, 2018)
Pericoma miljenkoi sp. nov. is described based on adult males from the Plitvička jezera National Park, Croatia. Pericoma trifasciata is recorded from Croatia for the first time, and COI DNA barcodes are given from specimens collected in Germany. An emended key to adult Pericoma of the trifasciata group is presented. The Croatian Psychodidae fauna now stands at 35 species.